Desenvolvimento de modelos de camada limite atmosférica aplicados a micro-regiões - Gilberto Augusto Amado Moreira (2012)
This study presents the development of a numerical model to analyze the Atmospheric Boundary Layer (ABL) in order to obtain the velocity fields and wind direction in micro-regions, considering the analysis of thermal effects in the present physical problem and the terrain roughness. The study of ABL is of great importance for design of overhead lines to transmit power in determining the balance of the insulator strings of power cables, in determining the transmission capacity of the airlines, in determining the diffusion of pollutants in the atmosphere, and others. The numerical modeling is performed using the commercial software Ansys CFX 12.0. The results of the numerical model are validated with experimental data found in literature and a database of experimental data obtained from measurements at weather stations located in regions of interest CEMIG in the state of Minas Gerais, Brazil. The equations used to describe geophysical flows are the mass, momentum, energy conservation and the equation of state, in addition to the turbulence models of two equations and the Reynolds stresses. Numerical modeling of ABL using computer techniques allows for the speed and direction of wind over complex terrain without the need for an experimental apparatus. The results of the present model fidelity with the experimental results, showing the validity of the model for both a neutral boundary layer and for a convective boundary layer.